Application of Freundlich and Temkin Isotherm to Study the Removal of Pb(II) Via Adsorption on Activated Carbon Equipped Polysulfone Membrane - Anwar Mohamad Said, Khairul; Zakirah Ismail, Nor; Liyana Jama'in, Ramizah; Ain Mohamed Alipah, Nurul; Mohamed Sutan, Norsuzailina; George Gadung, Genevieve; Baini, Rubiyah; Syuhada Ahmad Zauzi, Nur (International Journal of Engineering and Technology, 2018)
The aim of this study was to investigate the application of membrane equipped activated carbon for heavy metal removal. An adsorption capacity of the activated carbon inside membrane matrix was performed against environmentally problematic ions specifically Pb2+, in aqueous solution. The adsorption process was examined by Temkin and Freundlich isotherm. From the SEM observation, membrane exhibit sponge-like structure with dense micro-void formation across the matrix. This phenomenon was usually observed with membrane mixed with polyethyleneimine. For the adsorption studies, it is shown that Freundlich isotherm show better fit based on R2 value of 0.9893 with Temkin isotherm fitted with R2 of 0.9009. Through the fitted model, the adsorption occur on the surface of activated carbon are possibly multilayer type adsorption based on theory by Freundlich isotherm and fall under non-ideal reversible adsorption. Â Â